Critical Strategies for Drug Precipitation Inhibition: A Review with the Focus on Poorly Soluble Drugs - Parmar, Tanvi; Kadu, Pramod; Kale, Pravin (Current Drug Delivery, 2023)
An oral route for drug administration is a more suitable route because of its ease of administration, pain avoidance, patient compliance, accommodation of various types of drug molecules, etc. But there are many factors affecting the oral absorption of the drugs. The main factor associated with oral absorption is drug solubility. Many new chemical molecules are poorly soluble in nature and can be included in BCS classes II and IV. For the administration of these drugs through the oral route, it was found that solubility is the rate limiting step. The low solubility of these drugs tends to cause precipitation in the gastrointestinaltract (GIT), affecting their bioavailability. Drug precipitation may be triggered by many factors such as insolubility of the drug in co-solvent, drug-excipient interactions, physiochemical properties of the drug, sudden change in the pH of the environment, incompatibility with the surfactant, etc. Precipitation of a drug may occur in two stages, formation of nucleation and crystal growth. To overcome precipitation, there are many strategies such as the use of polymers, the addition of surfactants, modulating drug loading and solubilizing capacity, change in the pH of the environment, etc. In this review, the causes of precipitation and diverse strategies of precipitation inhibition are critically reviewed.
Keywords: crystal growth